آليات الرقابة الجبائية الحديثة ودورها في فحص الوضعية الجبائية الشاملة للمؤسسات الاقتصادية - بلخيري, محمد سعد الدين; مصمودي, أنيس (جامعة الوادي University of Eloued, 2020)
This study aimed to identify the roleof fiscal control in assessing the globatax situation of Algerian economicentities through the case aneconomicSPAentityaffiliatedto the Tax Center of Constantine, whichis a quarrylocated in Didouche Mourad in the wilaya of Constantine. We chose thisentitybecauseof the specificfeaturesof taxes imposed on the miningsectorsuch as the tax on the profits of mines IBM. Our resultsindicatethatfiscal control has a prominentrole in examining and diagnosing the taxsituation of the entity and monitoring the statements submitted by taxpayers, which would achieve a set of economic, social, and evenfinancial goals.
Modern tax control mechanisms and their role in increasing tax collection Case of an economic entity affiliated to the Tax Center of Constantine
مقال
Keywords: الرقابة الجبائية ; الإدارة الضريبية ; المكلف بالضريبة ; التصريحات الجبائية ; الضريبة على أرباح المناجم